2018
DOI: 10.1038/s41598-018-32112-y
|View full text |Cite
|
Sign up to set email alerts
|

EPR Imaging of Metallic Lithium and its Application to Dendrite Localisation in Battery Separators

Abstract: Conduction Electron Paramagnetic Resonance Imaging (CEPRI) is presented as a sensitive technique for mapping metallic lithium species. The method is demonstrated using different samples that are either thick or thin compared to the microwave skin depth. As a thin sample, microstructured metallic lithium deposits in a lithium-ion battery (LIB) separator were analysed, illustrating the capabilities of CEPRI by obtaining a high-resolution image with an image resolution in the micrometre range. Limitations and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 43 publications
0
58
0
Order By: Relevance
“…MRI is a powerful tool for studying chemical, biological, and solid-state phenomena (5)(6)(7)(8). Recently, in situ MRI of model electrochemical devices shed light on underlying physical and mechanistic processes (9)(10)(11)(12)(13)(14)(15)(16). These techniques however could not be used to study commercial cells due to the conductive casings and small distances between electrodes, which hamper radiofrequency (RF) penetration.…”
mentioning
confidence: 99%
“…MRI is a powerful tool for studying chemical, biological, and solid-state phenomena (5)(6)(7)(8). Recently, in situ MRI of model electrochemical devices shed light on underlying physical and mechanistic processes (9)(10)(11)(12)(13)(14)(15)(16). These techniques however could not be used to study commercial cells due to the conductive casings and small distances between electrodes, which hamper radiofrequency (RF) penetration.…”
mentioning
confidence: 99%
“…Previous EPR investigations showed that the lineshape, linewidth and integrated intensity were highly dependent on the morphology of metallic lithium 6,7,9 . The EPR spectrum lineshape of a metallic conductor is indeed controlled by the limited penetration depth δ mw of the microwave field in the metal, known as the skin effect 10 :…”
Section: Resultsmentioning
confidence: 97%
“…In continuation of the latter an extensive study by operando EPR spectroscopy was performed for Li plating on graphite 8 . Niemöller et al also studied, ex situ, the potential and limitations of ex situ EPR imaging (EPRI) on metallic Li 9 .…”
mentioning
confidence: 99%
“…Neimöller et al used CEPR to study dendrite growth on separator. [212] They explained how the EPR line shape serves to distinguish different kinds of Li morphologies. EPR of conductive samples are influenced by the skin effect, which leads to a depth dependent attenuation and sample thickness dependent phase shift of the EPR signal [211,213] .…”
Section: Electron Paramagnetic Resonancementioning
confidence: 99%
“…Reproduced from Neimöller et al Scientific Reports, 8, 14331 (2018). [212] . (CC BY, https://creativecommons.org/licenses/by/4.0)…”
Section: Electron Paramagnetic Resonancementioning
confidence: 99%